2015
DOI: 10.3906/biy-1402-62
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of various lactic acid bacteria on Caco-2 cells

Abstract: Probiotics are live microbial food supplements that can be considered a functional food. They benefit the health of a host animal by maintaining their intestinal microbial balance. Most probiotic microorganisms are lactic acid bacteria (LAB) such as Lactobacillus spp., Bifidobacterium spp., and Enterococcus spp. LAB have been reported to possess certain anticancer properties. The vast majority of studies on their anticancer effects have dealt with colorectal cancers, although there have also been some studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 37 publications
3
16
1
Order By: Relevance
“…CFS exhibited stronger inhibition on the cancer cells than BC. This is in parallel to the findings reported by Er, Koparal, and Kivanc (2015) that Pediococcus pentosaceus, L. plantarum and Weissella confusa isolated from fermented meat were able to inhibit the growth of colon cancer cells in a dose-dependent manner and, more interestingly, cell-free filtrate of L. plantarum also showed stronger effects compared with the other two strains. Our findings are also in accordance with a previous study by Haghshenas et al (2015) which demonstrated that secreted metabolites of L. plantarum 17C isolated from ewe colostrum exhibited antiproliferative effect on HT-29 cell line.…”
Section: Discussionsupporting
confidence: 90%
“…CFS exhibited stronger inhibition on the cancer cells than BC. This is in parallel to the findings reported by Er, Koparal, and Kivanc (2015) that Pediococcus pentosaceus, L. plantarum and Weissella confusa isolated from fermented meat were able to inhibit the growth of colon cancer cells in a dose-dependent manner and, more interestingly, cell-free filtrate of L. plantarum also showed stronger effects compared with the other two strains. Our findings are also in accordance with a previous study by Haghshenas et al (2015) which demonstrated that secreted metabolites of L. plantarum 17C isolated from ewe colostrum exhibited antiproliferative effect on HT-29 cell line.…”
Section: Discussionsupporting
confidence: 90%
“…Chui and coworkers reported similar results, L. plantarum co-cultured with Caco-2 cells did not affect cell viability within 10 h, but cell viability decreased significantly between 12 and 14 h but the decreases was non-significant [67]. The inhibitory effects of probiotics upon the proliferation of several colon cancer cell lines have been previously demonstrated by various authors [38,[68][69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 57%
“…These results are in harmony with previous studies showing that various probiotic bacteria had no cytotoxic effect on Caco-2 cells. For instance, Er et al (2015) studied the cytotoxicity of three LAB ( Pediococcus pentosaceus, Lactobacillus plantarum , and Weissella confusa ) on Caco-2 cells and showed dose-dependent cytotoxic effects of the cell-free filtrates and cell-free lyophilized filtrates of the three LAB. Similarly, a recent work performed by Castro et al (2016) demonstrated that E. faecalis CECT7121 strain is not cytotoxic for Caco-2 cells.…”
Section: Resultsmentioning
confidence: 99%